Process approach: A problem-based learning methodology in operations management - C. L., Yee (Edward Elgar Publishing, 2024)
The field of operations management (OM) has long been regarded as lacking industrial rel- evance to managerial practice. The knowledge produced by universities is neglected by the practising world. Thus, this has created a theory and practice gap. The debate about the theory and practice gap has been extensive in recent years. The criticism about industrial relevance in management has its roots in the field of economics. Economics always treats mathematical modelling as an end in itself and ignores the realities. Thus, this has led to blindly search- ing for law-like generalisations in research. This is because the closed-system mathematical modelling methods are not appropriate for the open-structured, dynamic and fast-changing systems characteristics of the social world. As a result, the theory and practice gap has been widened between academics and the practising world.